Implementasi Load Balancing Web Server Menggunakan Apache di Ubuntu 16.04. - Kresno Wibowo; Iskandar Fitri; Deny Hidayatullah (STMIK PONTIANAK, 2020)
When many users access a website at the same time. So when it can make the web server to accommodate excessive loads because it can no longer accommodate the number of requests received. And that usually happens when a single web server or single. However, using the Round Robin load balancing method and also Haproxy as a load balancer can help regulate load sharing on each server. With testing done on 250 users, 500 users, 750 users, up to 1000 users and using a static web. So you can see the CPU usage that is used by the user load that is tested at the time after performing. The results of testing using haproxy run better than a single server and two servers. By using Apache benchmark in calculating Throughput and Time per request between a single server, two servers and running all servers using Haproxy. For testing the presentation on the CPU that is used on 250 users is 31.9% the lowest but there is an increase in testing 1000 users, reaching 54.5%. The test results on two servers in testing 250 users, 500 users, 750 users, and 1000 users produced 62.5% -68.7% results. And by testing on a single server RAM usage in testing 250 users, 500 users, 750 users, and 1000 users which reached about 91% -96%. With better test results using haproxy load balancing than using a single server or two servers. Because the use of a single server and two servers almost reached overload. Which means the time needed to handle the load is load balancing using haproxy better than a single server to more quickly handle requests, time per second and CPU usage.